Gethebook - Adnan, Imran Hakim; Johari, Nor Imani Shazline; Ruslan, Aniqah Rusyda; Dahari, Siti Nur Shahira (Universiti Teknologi MARA, Kedah, 2019)
"Gethebook" is one of technology that can help all users or patrons to reach out the materials for them. It is using QR code and smartphone. This is because nowadays all users and patrons have their own smartphone so this will make them easier to retrieve and use our "Gethebook". We are focusing this to users and patrons who do not know how to search book at the library. The first step is, users must search requested book at the OPAC then the QR code will be provided to them. Besides, this technology provides guide to help all user and patron to search their library material.